Catalytically active ceria-supported cobalt–manganese oxide nanocatalysts for oxidation of carbon monoxide. Issue 22 (24th May 2017) - Wang, Xu; Du, Lin-Ying; Du, Meng; Ma, Chao; Zeng, Jie; Jia, Chun-Jiang; Si, Rui
Abstract : The crystallinity of the surface of the two-dimensional Co3 O4 phase governs the catalytic performance of ceria-supported cobalt–manganese oxide nanostructures. Abstract : A low-concentration cobalt (∼6 at%) and manganese (∼3 at%) bimetallic oxide catalyst supported on ceria nanorods (CoMnO x /CeO2 ), as well as its related single metal oxide counterparts (CoO x /CeO2 and MnO x /CeO2 ) was synthesized via a deposition–precipitation approach. The fresh samples after air-calcination at 400 °C were tested under the reaction conditions of CO oxidation, and showed the following order of reactivity: CoMnO x /CeO2 > CoO x /CeO2 > MnO x /CeO2 . X-ray diffraction (XRD) and transmission electron microscopy (TEM) data identified that the structure of the CeO2 support was maintained during deposition of metal (Co, Mn) ions while the corresponding vis-Raman spectra verified that more oxygen vacancies were created after deposition–precipitation than those in pure ceria nanorods. Aberration-corrected, high-angle, annular dark-field scanning transmission electron microscopy (HAADF-STEM) images with the help of electron energy loss spectroscopy (EELS) analyses determined two types of cobalt species, i.e. ultra-fine clusters (<2 nm) and smaller nanocrystals (up to 5 nm) in CoO x /CeO2 while only bigger nanostructures (∼10 nm) of cobalt–manganese oxides in CoMnO x /CeO2 . X-ray absorption fine structure (XAFS) measurements demonstrated the presence of a cubic Co3 O4 phase in all the cobalt-based catalysts. The fitting results of the extended X-ray absorption fine structure (EXAFS) indicated that the introduction of the secondary metal (Mn) oxide significantly enhanced the two-dimensional growth of cobalt oxide nanostructures on the surface of CeO2 . Therefore, the enhanced activity of CO oxidation reaction over the bimetallic cobalt–manganese oxide nanocatalyst can be attributed to the higher crystallinity of the Co3 O4 phase in this work.